Fundamentals of continuum mechanics - Rudnicki, John W (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc, 2015)
'Fundamentals of Continuum Mechanics focuses on the fundamentals of the subject and provides the background for formulation of numerical methods for large deformations and a wide range of material behaviours'--
Includes bibliographical references and index.
Keywords: Continuum mechanics